MODEL KOOPERATIF STAD DAPAT MENINGKATKAN HASIL BELAJAR PASSING BAWAH BOLA VOLI PADA SISWA - Nurdin, Nurdin (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
The background of this research is that the ability to pass under volleyball is still lacking, this is evidenced by many of the students who have not been able to do underpass perfectly. One of the causes of the failure of the learning process is the application of the learning method which emphasizes the domination of the teacher’s role. This study is to determine the increase in the results of underhand passing learning in volleyball through the application of the STAD cooperative model. The sample consisted of 23 students. The instrument is used to measure the success of teacher and student activities in teaching and learning activities by using observation sheets, while for student learning outcomes is with cognitive, affective and psychomotor tests. This research includes classroom action research or classroom action research. Data were analyzed using presentation techniques. The data analysis technique used was descriptive analysis techniques where in cycle I the level of completeness of teacher activities in carrying out learning activities reached 65.21% and increased in cycle II to 91.30%, this has exceeded the standard based on the minimum completeness criteria, namely 75%, while student learning outcomes in the first cycle only reached 65.21%, increasing in the second cycle to 91.30% or more to reach the level of learning completeness set by the school, namely 75%. Thus it can be concluded that the application of the STAD cooperative model can improve the learning outcomes of volleyball under-passing in students